A concept of integrated environmental approach, Part 2: Integrated approach to rehabilitation. (May 2016) - Bomberg, Mark; Wojcik, Robert; Piotrowski, Jerzy
In the first part of this series, we discussed that the building structure, energy efficiency, indoor environmental quality, and moisture management all need to be considered simultaneously to ensure durability of materials and control cost of near-zero energy buildings. These factors must be addressed through contributions of the whole design team. It is also evident that building physics must take an active role in development of near-zero energy buildings . The need to ensure good indoor environment and durability of materials and limit the cost of buildings led to integrated design process that now is typical in Canada for design of low-energy buildings. Furthermore, interactions between energy efficiency, quality of indoor environment and moisture management led us to introduce a concept of "environmental control." In the meantime, we made an unexpected observation—Vancouver dwellings in 2002 use the same amount of energy as 1920 uninsulated masonry buildings erected in the same location. We concluded that despite having advanced technology, our lack of vision prevents us from an effective use of this technology. With the quest for sustainable buildings, we should learn more from termites, who appear to master the art of hygrothermal control better than humans as they are capable of maintaining highly stable interior comfort zone without heating, ventilating, and air-conditioning equipment. Nevertheless, whatever progress is achieved in new low-energy buildings, it is lost when rehabilitating existing buildings because there an owner will typically do one step at a time. If the financial constraints do not allow for more, this first step should be an integrated action that includes a combination of insulation and heating systems.